TRPM4 expression is associated with activated B cell subtype and poor survival in diffuse large B cell lymphoma. Issue 1 (27th April 2017) - Loo, Suet K; Ch'ng, Ewe S; Md Salleh, Md Salzihan; Banham, Alison H; Pedersen, Lars M; Møller, Michael B; Green, Tina M; Wong, Kah K
Abstract : Aims: Transient receptor potential channel melastatin 4 (TRPM4) is an ion channel that regulates influx of calcium cations (Ca 2+ ). Recent studies suggest that TRPM4 is an oncoprotein, and its up‐regulated transcript level has been reported in diffuse large B cell lymphoma (DLBCL). We aimed to investigate TRPM4 protein expression pattern in non‐malignant tissues and DLBCL cases, and its association with clinico‐demographic parameters and survival in DLBCL. Methods and results: Analysis of publicly available DLBCL microarray data sets showed that TRPM4 transcripts were up‐regulated in DLBCL compared to normal germinal centre B (GCB) cells, were expressed more highly in the activated B cell‐like DLBCL (ABC‐DLBCL) subtype and higher TRPM4 transcripts conferred worse overall survival (OS) in R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone)‐treated DLBCL cases ( P < 0.05). Our immunohistochemical analysis showed that TRPM4 was expressed in various human tissues but not in normal B cells within lymphoid tissues (reactive tonsil, lymph node and appendix). TRPM4 protein was present in 26% ( n = 49 of 189) of our cohort of R‐CHOP‐treated DLBCL cases and this was associated significantly with more aggressive clinical parameters, including higher lactate dehydrogenase (LDH), Eastern Cooperative Oncology Group (ECOG) scores or stage ( P < 0.01 for each of the parameters) and the ABC‐DLBCL subtype ( P = 0.016). TRPM4 positivity conferred significantly worse OS ( P = 0.004) and progression‐free survival (PFS) ( P = 0.005). Worse OS remained associated significantly with TRPM4 positivity in multivariate analysis, including higher International Prognostic Index (IPI) or the non‐GCB DLBCL phenotype ( P < 0.05). Conclusions: TRPM4 protein expression is up‐regulated in DLBCL cases compared to non‐malignant B cells with preferential expression in ABC‐DLBCL cases, and it confers significantly poorer DLBCL patient outcomes.